Radical social work in practice : making a difference. - Ferguson, Iain, ....-; Woodward, Rona, ....- (Bristol : Policy Press, 2009)
Radical social work is a tradition often identified exclusively with the movement which developed in the UK in the 1970s, yet as this much-needed new textbook demonstrates, the relevance of radical approaches to contemporary social work practice have never been stronger. Challenges to a neoliberal approach to social work have been gaining ground academically, and, to a lesser extent, in practice circles. This book provides a fresh understanding of the radical tradition and shows how it can be developed in contemporary social work. Using case studies to illustrate the type of dilemmas faced by workers in their day-to-day practice, the book sets out the ways in which a radical social work approach can inform constructive responses. The book emphasises the need to understand the diverse lives of service users, encouraging readers to share experience and knowledge and to discuss past and present events, to build confidence in tackling injustice at individual and societal levels. As many social
Workers are becoming disillusioned and dissatisfied with the profession, this book promotes a practice that is rooted in a commitment to positive change and to social justice that will offer a breath of fresh air to students and practitioners alike. Dr Iain Ferguson worked for many years as a social worker and community worker in various settings in the west of Scotland. He currently teaches social work at the University of Stirling. He is the author of "Reclaiming Social Work: Challenging Neo-liberalism and Promoting Social Justice" (Sage, 2008) and is a co-founder of the Social Work Action Network. Rona Woodward qualified as a social worker in 1990 and worked in local authority social work services in London and the east of Scotland for 10 years, with a particular interest in children and young people at risk or in need, including young offenders. Having taken her MSc in criminal justice in 1999, she worked as a criminology researcher at Edinburgh University and taught social work at Glasgow
Caledonian University before taking up her current post as lecturer in social work at Stirling in April 2004. She is an active member of the Social Work Action Network. Contents Social work in a divided society The radical kernel Neo-liberalism and social work State social work: constraints and possibilities The 'third sector': a radical alternative? Beyond good intentions: the challenge from service users and carers Rediscovering collective approaches Conclusion: social work, a profession worth fighting for
Keywords: Sociaal werk